Is It Necessary to Perform the Second Surgery Stage of Anterior Debridement in the Treatment of Spinal Tuberculosis? - Liao, Yehui; Ye, Rupei; Tang, Qiang; Tang, Chao; Ma, Fei; Luo, Ning; Zhong, Dejun (World neurosurgery, 2020)
In this retrospective comparative study, the efficacy and clinical outcomes of long posterior instrumentation, with or without laminectomy, were evaluated and the necessity of the second stage of anterior debridement in the treatment of spinal tuberculosis (TB) was discussed. This retrospective study included 41 patients who were diagnosed with spinal TB between January 2010 and June 2016. A total of 18 patients had received long posterior instrumentation, with or without laminectomy (group A), whereas the other 23 patients had posterior instrumentation plus anterior debridement and autogenous bone grafting (group B). The surgical information, clinical effectiveness, laboratory tests, and imaging results were compared between the 2 groups. One patient in group B died. Sinus drainage and incomplete bone fusion were discovered 1 year postoperatively. TB symptoms were significantly improved after surgery compared with those before surgery (P < 0.05), and there was no significant difference in the treatment efficacy between the 2 groups at the final follow-ups (P > 0.05). Compared with those of group B, the surgical time, bed-rest time, and hospitalization time of group A were all significantly shorter (P < 0.05), whereas the times before abscesses disappeared, bone graft fusion, and erythrocyte sedimentation rate returning to normal were all significantly longer (P < 0.05). Single-stage long posterior instrumentation, with or without laminectomy, is a safe, effective, and feasible method for the treatment of spinal TB. The second stage of anterior debridement surgery may not be necessary for every spinal TB treatment.